Bifidobacteria in the digestive tract of bumblebees - Killer, Jirí; Kopecný, Jan; Mrázek, Jakub; Rada, Vojtech; Dubná, Sona; Marounek, Milan (Anaerobe, 2010)
Bifidobacteria and other bacterial groups (lactobacilli, facultative anaerobes, anaerobes) from the digestive tract of three bumblebee species (Bombus lucorum (34 samples), Bombus pascuorum (18 samples) and Bombus lapidarius (9 samples)) were enumerated and characterised. Counts of facultative anaerobic bacteria and lactobacilli (5.41+/-2.92 and 2.69+/-3.02 log CFU/g of digestive tract content) were lower than those of anaerobes (7.66+/-0.86 log CFU/g). Counts of bifidobacteria were determined using two selective media: MTPY (Modified Trypticase Phytone Yeast extract agar) and a new medium with pollen extract. There was no significant difference between the counts of bifidobacteria from both media, 5.00+/-2.92 log CFU/g on MTPY and 5.00+/-2.87 on the pollen medium. Subsequently, 187 bacterial strains of the family Bifidobacteriaceae (fructose-6-phosphate phosphoketolase-positive) were isolated from three different localities and from all three species of bumblebees. Bifidobacteria were found in 42 out of 61 specimens (69%). Twenty-three (38%) specimens had counts of bifidobacteria higher than 7.0 log CFU/g. Bifidobacteria represented the dominant group of anaerobes (>70% of total anaerobes), i.e., the principal group of bacteria in the bumblebee digestive tract, in only fourteen specimens (23% of total). For the first time, bifidobacteria were isolated from the digestive tract of bumblebees. In addition, we suggest, on the basis of biochemical tests (API 50 CHL and RAPID ID 32) and genetic methods (PCR and DGGE), that these bacteria may represent new species within the family of Bifidobacteriaceae.
Keywords: Animals; Electrophoresis, Polyacrylamide Gel; DNA bakterií; DNA Fingerprinting; bakteriální proteiny; bakteriologické techniky; Bacteriological Techniques; Bacterial Proteins; RNA, Ribosomal, 16S; DNA, Bacterial; shluková analýza; Aldehyde-Lyases; denaturace nukleových kyselin; počet mikrobiálních kolonií; gastrointestinální trakt; DNA fingerprinting; Colony Count, Microbial; Culture Media; aldehydlyasy; Phylogeny; kultivační média; Bees; Bacterial Typing Techniques; Sequence Analysis, DNA; techniky typizace bakterií; Actinobacteria; včely; zvířata; sekvenční analýza DNA; Gastrointestinal Tract; Cluster Analysis; fylogeneze; elektroforéza v polyakrylamidovém gelu; Nucleic Acid Denaturation; RNA ribozomální 16S